2018
DOI: 10.15376/biores.13.2.3659-3673
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Mechanical Characterization of Electrospun Polylactic Acid and Microcrystalline Cellulose

Abstract: The goal of this work was to develop a composite material, a membrane, based on polylactic acid (PLA) reinforced with cellulose microcrystalline (MCC). Membranes based on PLA were fabricated using electrospinning. The fabrication parameters, fiber morphology, and mechanical properties were analyzed. For fabrication, 12 mL of solution (12%, weight basis, of PLA in chloroform) was used and three different injector-collector distances and three voltages were employed. The fiber morphology was observed using a sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…This relatively high tensile strength compared to others is due to the 3 D honeycomb structure of the fibre produced. Recent results on microcrystalline cellulose electrospun PLA fibres presented by Gaitan and Gacitua, (2018) are lower than those obtained in this study at the same filler weight fraction. Chen and Liu (2008) also obtained lower tensile strength at the same filler weight fraction using cellulose nanocrystals soybean protein fibre.…”
Section: Effects Of Processing Parameters On Tensile Properties Of Elcontrasting
confidence: 88%
“…This relatively high tensile strength compared to others is due to the 3 D honeycomb structure of the fibre produced. Recent results on microcrystalline cellulose electrospun PLA fibres presented by Gaitan and Gacitua, (2018) are lower than those obtained in this study at the same filler weight fraction. Chen and Liu (2008) also obtained lower tensile strength at the same filler weight fraction using cellulose nanocrystals soybean protein fibre.…”
Section: Effects Of Processing Parameters On Tensile Properties Of Elcontrasting
confidence: 88%
“…In addition, an improvement in the interfacial adhesion between the PLA-PEG matrix and MgSiO 3 , as can be observed in the next morphology section, is also effective in transferring the stress during breaking, as well as propagation of cracks [33]. It is interesting to note that the strengthening of mechanical properties may also be caused by the interaction ensued in the PLA-PEG/MgSiO 3 membrane where a hydrogen and covalent bond could be formed, with the assistance of hydroxyl and silane functional groups, between membrane matrix and filler [34]. This finding can be supported by a previous report which demonstrated that the increased amount of filler in a membrane may enhance the tensile properties of the material [35].…”
Section: Mechanical Propertiesmentioning
confidence: 66%
“…Cellulose, a plant derivative is the main structural fiber in the plant kingdom and is known to possess remarkable mechanical properties for a polymer as its Young's modulus is estimated as roughly 130 (gigaPascal) gPa while its tensile strength is close to 1 gPa [1]. Besides this attribute, cellulose and its derivatives has over time regained prominence as a source of obtaining pharmaceutical excipients because of its natural abundance and availability, low cost, eco-friendliness, non-toxicity and ease of processing [2].…”
Section: Introductionmentioning
confidence: 99%